Communication Challenges for Foreign Workers within Multicultural Hospitality Working Environment: Case Front Office of Hotel X in Japan - Basalamah, Anwar; Ardani, Edvi Gracia; Fransisca, Angeline (Universitas Pendidikan Ganesha, 2021)
As tourism grows fast and tourism destinations develops well all around the world, the human capital in the sectors are the most important component of its business which deliver services. The grow affects all aspects of business including hospitality industry. A multicultural working environment in hospitality industry has been practiced since decades due to its international character of business. The condition brought communication challenges to the internal operations more particularly in the front-line departments. This study aims to find out the challenges for foreign workers in the process of communication and how they overcome any communication problems that may occurred in their day-to-day operations in a multicultural hospitality working environment. Different cultures may press the communication problems while the business is about serving people and ensure that all the guest needs are provided well in timely manner. The research is conducted in a three-star-rated hotel in Japan with a multicultural environment and may give insights to the hoteliers who aspire to embrace their future career abroad. The findings are quite interesting since culture is taking the most important part to overcome and handle the situation as it aims to maintain a good working environment.